Unbound (Free) Bilirubin: Improving the Paradigm for Evaluating Neonatal Jaundice - Ahlfors, Charles E; Wennberg, Richard P; Ostrow, J. Donald; Tiribelli, Claudio (Clinical chemistry (Baltimore, Md.), 2009)
Background: The serum or plasma total bilirubin concentration (BT) has long been the standard clinical laboratory test for evaluating neonatal jaundice, despite studies showing that BT correlates poorly with acute bilirubin encephalopathy (ABE) and its sequelae including death, classical kernicterus, or bilirubin-induced neurological dysfunction (BIND). The poor correlation between BT and ABE is commonly attributed to the confounding effects of comorbidities such as hemolytic diseases, prematurity, asphyxia, or infection. Mounting evidence suggests, however, that BT inherently performs poorly because it is the plasma non–protein-bound (unbound or free) bilirubin concentration (Bf), rather than BT, that is more closely associated with central nervous system bilirubin concentrations and therefore ABE and its sequelae. Content: This article reviews (a) the complex relationship between serum or plasma bilirubin measurements and ABE, (b) the history underlying the limited use of Bf in the clinical setting, (c) the peroxidase method for measuring Bf and technical and other issues involved in adapting the measurement to routine clinical use, (d) clinical experience using Bf in the management of newborn jaundice, and (e) the value of Bf measurements in research investigating bilirubin pathochemistry. Summary: Increasing evidence from clinical studies, clinical experience, and basic research investigating bilirubin neurotoxicity supports efforts to incorporate Bf expeditiously into the routine evaluation of newborn jaundice. .